Modeling of Micro-Scale Catalytic Reactor for Hydrogen Production - Mohd Syazwan Hafiz bin Abd Aziz, Mohd Syazwan Hafiz (Universiti Teknologi Petronas, 2011)
The purpose of this report is to discuss on the research that has been done entitled Modeling of Micro-Scale Catalytic Reactor for Hydrogen Production. The project work focuses on the modeling and simulation of a 2-dimensional autothermal reforming reactor by using the COMSOL software. Autothermal reforming reactor (ATR) is a process that combines total methane combustion and steam methane reforming within the catalyst beds inside a reactor. The main objective for this project is to analyze the effect of varying parameters towards the behavior inside the reactor. The variables in this study are catalyst porosity, water-fuel ratio (W/F ratio) and reforming channel size. The reactor behavior is investigated by looking into its concentration, temperature and velocity profiles. Simulation was carried out by referring experimental data as its basis, in order to validate the model first, before continuing to simulate other variable cases. Based on the simulation results obtained, higher catalyst porosity will increase the CH4 concentration and overall temperature in both combustion and reforming section, while decreasing the CH4 conversion and the velocity at the centre of both combustion and reforming channels. No significant effects can be observed in the combustion section when the W/F ratio changes. On the other hand, the CH4 concentration and overall temperature becomes lower when W/F ratio is increasing in the reforming section. Overall reforming velocity also increases. Similar to W/F ratio, reforming channel size only affects the profiles inside the reforming section. When bigger channel size is used, CH4 concentration and the overall temperature of reforming section become higher.